EARLY CRETACEOUS GABBROIC ROCKS FROM THE TAIHANG MOUNTAINS: IMPLICATIONS FOR A PALEOSUBDUCTION-RELATED LITHOSPHERIC MANTLE BENEATH THE CENTRAL NORTH CHINA CRATON - Wang Y.; Fan W.; Peng T.; Zhang H. (My University, 2006)
SHRIMP zircon U-Pb ages and geochemical and Sr-Nd-Pb isotopic data are presented for the gabbroic intrusive from the southern Taihang Mountains to characterize the nature of the Mesozoic lithospheric mantle beneath the central North China Craton (NCC). The gabbroic rocks emplaced at 125 Ma and are composed of plagioclase (40-50%), amphibole (20-30%), clinopyroxene (10-15%), olivine (5-10%) and biotite (5-7%). Olivines have high MgO (Fo = 78-85) and NiO content. Clinopyroxenes are high in MgO and CaO with the dominant ones having the formula of En42-46Wo41-50Fs8-13. Plagioclases are dominantly andesine-labradorite (An = 46-78%) and have normal zonation from bytownite in the core to andesine in the rim. Amphiboles are mainly magnesio and actinolitic hornblende, distinct from those in the Precambrian high-pressure granulites of the NCC. These gabbroic rocks are characterized by high MgO (9.0-11.04%) and SiO2 (52.66-55.52%), and low Al2O3, FeOt and TiO2, and could be classified as high-mg basaltic andesites. They are enriched in LILEs and LREEs, depleted in HFSEs and HREEs, and exhibit (87Sr/86Sr)i = 0.70492-0.70539, εNd(t) = - 12.47-15.07, (206Pb/204 Pb)i = 16.63-17.10, Δ8/4 = 70.1-107.2 and Δ7/4 = - 2.1 to - 9.4, i.e., an EMI-like isotopic signatures. Such geochemical features indicate that these early Cretaceous gabbroic rocks were originated from a refractory pyroxenitic veined-plus-peridotite source previously modified by an SiO2-rich melt that may have been derived from Paleoproterozoic subducted crustal materials. Late Mesozoic lithospheric extension might have induced the melting of the metasomatised lithospheric mantle in response to the upwelling of the asthenosphere to generate these gabbroic rocks in the southern Taihang Mountains. © 2005 Elsevier B.V. All rights reserved.
Keywords: CENTRAL NORTH CHINA CRATON; EARLY CRETACEOUS GABBROIC ROCKS; EM1-LIKE LITHOSPHERIC MANTLE; SHRIMP ZIRCON DATING; TAIHANG MOUNTAINS; Cretaceous; Paleoproterozoic; Mesozoic::Cretaceous; Мезозой::Меловая; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская